SHAXSLARARO MUNOSABATLARDA QORA VA YORQIN UCHLIKLARNING MANIPULYATIV MEXANIZMLARI (Multidisciplinary Journal of Science and Technology, 2026)
The article analyzes a person's manipulative behavior based on the constructs of the "black triad" (machiavellianism, narcissism, psychopathy) and the "bright triad" (humanism, virtue, cantinism). It is shown that "black trio" strategies lead to short-term benefits, distrust, and conflicts, while "bright trio" holders are focused on strengthening cooperation and mutual trust. The significance of these structures in harmonizing with national values and ensuring social stability in the conditions of Uzbekistan is also highlighted.